Caracterização bioquímica e biológica da peçonha de Tityus confluens - Laís Corrêa de Lima (2023)
Scorpions are arthropods from Scorpiones, habit several ecosystems, and are venomous animals with a venom-inoculating structure, causing accidents in humans. These accidents are considered a public health problem in several countries, such as Brazil, however, only 50 species of the more than 2700 that have already been described are responsible for accidents, and in Brazil, all are from the genus Tityus. Venoms are complex mixtures, composed of bioactive molecules, with promising potential for prospecting new biotechnological and pharmacotherapeutic products. However, few studies about the venom of several scorpions, such as Tityus confluens, occur in the Brazilian savanna. The present study aimed to characterize biochemically and biologically the venom from Tityus confluens. The protein and chromatographic profile of the venom was verified, as well as the enzymatic activities, such as phospholipase, amylolytic and proteolytic, the effect of the venom on the activity of membrane ATPases, in addition to evaluating the cytotoxicity on normal and tumor cells. The venom showed a diversity of components by the electrophoretic and chromatographic profile, showing protein bands with molecular masses between 50 -100 kDa, bands smaller than 10kDa, and eluted fractions between 18 - 25 min of RT and the largest fraction at 41 min of RT, possibly corresponding to peptides. The venom caused an increase in the activity of ATPase enzymes when incubated at 30 and 50 min, demonstrated amylolytic activity, did not present phospholipase and proteolytic activities, and was not cytotoxic against normal and neoplastic cells. The results obtained in this study allow an initial characterization of the composition of the venom of Tityus confluens, expanding the view of scorpion venoms and further studies on these compounds are necessary to elucidate the potential molecules for bioprospecting.